Evaluation of mean platelet volume and platelet count in patients with hidradenitis suppurativa - Alkım Ünal (Galenos Publishing House, 2021)
Background and Design: Hidradenitis suppurativa (HS) is a chronic inflammatory condition of the apocrine glands. The mean platelet volume (MPV) is a risk factor for many inflammatory diseases and can be used as a marker of inflammatory response. This study aimed to evaluate the MPV and platelet count in patients with HS and compare them with those of healthy controls. Materials and Methods: Between September 2014 and October 2019, 97 patients diagnosed with HS and 78 healthy controls were included. Their MPVs and platelet counts were compared retrospectively. Results: The MPV was 10.17±0.94 in the patient group and 9.53±0.63 in the control group, with the difference being significant (p<0.05). No significant difference was noted between the groups in terms of platelet values. Conclusion: The MPV was significantly higher in patients with HS than in healthy controls. Based on this finding, the MPV may be used as an inflammatory marker in this patient group.